KONSEP WELFARE STATE AL MAWARDI DALAM KITAB ADAB AL-DUNYÄ€ WA AL-DÄªN: Sebuah Telaah konsep analisis kritis: KONSEP WELFARE STATE AL MAWARDI DALAM KITAB ADAB AL-DUNYÄ€ WA AL-DÄªN: Sebuah Telaah konsep analisis kritis - Stianto, Aris; Syamsuri, Syamsuri (Universitas Muhammadiyah Prof DR HAMKA, 2019)
This article tries to examine the concept of welfare state according to capitalism in the view of al-Mawardi. The process of data collection is done by studying books, articles that discuss the concept of welfare, especially the book of al Adab Dunya wa al-Din, the phenomenal work of Imam Al-Mawardi. Finally, this article explains that the concept of al-Mawardi's welfare state with the welfare state according to capitalism is the opposite. One of the most important examples of al-Mawardi's view in the welfare state is that religion is the basis of the state. So that the basic policy is always thinking about the benefit of the people not on the will of a particular group or group. It is different from the concept of capitalism that the existence of this welfare state is to cover up the failure of the economic system that has been applied. This study is very useful to know how the concept of welfare state according to capitalism and according to Al-Mawardi, as well as to be used as reference material in subsequent writings. Keyword: Welfare State, Al-Mawardi, Kapitalisme